DEVELOPMENT OF INTERACTIVE MULTIMEDIA MATERIALS ON ANIMAL CLASSIFICATION BASED ON FOOD CATEGORY AT GRADE V ELEMENTARY SCHOOL - Dinda Tiasna Maharani; Mahmud Alpusari; Neni Hermita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper reports a developmental product in the form of interactive multimedia on animal classification material based on food category in class V SD with valid and practical criteria. The method used is the Research and Development (RnD) method with the Plomp model. The Plomp model is carried out in three phases, namely Preliminary Research, Development or Prototyping, and Assessment. The researcher tested the validity of three validators, which consist of media, material experts, and language experts or linguists. To see the practicality of the product that is developed, the researcher conducted a limited trial in the form of a small group trial with teachers and students. The results of the validity test indicate that the developed interactive multimedia was in a very valid category with a percentage of 93.205%. Meanwhile, the practicality of interactive multimedia based on the teacher's response questionnaire was 90.55% in the very practical category and based on the student questionnaire the percentage was 92.25% in the very practical category. Based on the results of the research, it can be inferred that interactive multimedia meets valid and practical criteria, so it is recommended to apply it on natural science learning subjects at school.